Lavandula viridis L´Hér. Essential Oil Inhibits the Inflammatory Response in Macrophages Through Blockade of NF-KB Signaling Cascade - Zuzarte, Monica; Francisco, Vera; Neves, Bruno; Liberal, Joana; Cavaleiro, Carlos; Canhoto, Jorge; Salgueiro, Lígia; Cruz, Maria Teresa (Frontiers in Pharmacology, 2022)
Lavandula viridis L´Hér. is an endemic Iberian species with a high essential oil yield and a pleasant lemon scent. Despite these interesting features, this species remains unrecognized and poorly explored by the food and pharmaceutical industries. Nevertheless, it has been valued in traditional medicine being used against flu, circulatory problems and to relieve headaches. Since these disorders trigger inflammatory responses, it is relevant to determine the anti-inflammatory potential of L. viridis L´Hér. essential oil in an attempt to validate its traditional use and concomitantly to increment its industrial exploitation. Therefore, in the present study the chemical composition of this volatile extract as well as the effect on ROS production, inflammatory response and proteasome activity on LPS-stimulated macrophages were disclosed. Also, its safety profile on keratinocytes, hepatocytes and alveolar epithelial cells was depicted, envisioning a future human administration. The essential oil was characterized by high quantities of 1,8-cineole, camphor and α-pinene. From a pharmacological point of view, the essential oil showed a potent antioxidant effect and inhibited nitric oxide production through down-modulation of nuclear factor kappa B-dependent Nos2 transcription and consequently iNOS protein expression as well as a decrease in proteasomal activity. The anti-inflammatory activity was also evidenced by a strong inhibition of LPS-induced Il1b and Il6 transcriptions and downregulation of COX-2 levels. Overall, bioactive safe concentrations of L. viridis L´Hér. essential oil were disclosed, thus corroborating the traditional usage of this species and paving the way for the development of plant-based therapies.